SECTORAL LINGUISTIC AND UKRAINIAN STUDIES - Онкович, Ганна; Адамія, Зоя (Науковий вісник Ужгородського університету. Серія Філологія, 2023)
Linguistic and country studies issues have gained intensive development in Ukraine, in particular in the methodology of teaching Ukrainian to foreigners. The achievements of Ukrainian theorists and practitioners have aroused considerable interest among researchers of the linguistic teaching process. By introducing linguo-Ukrainian studies, Ukrainian scholars successfully developed this area in the methodology of teaching Ukrainian as a foreign language and sought to expand their research in this promising and relevant field. Nowadays, both linguistic studies and linguistic Ukrainian studies are successfully developing in Ukraine. The article presents the historical context of the term linguoculturology and proposes a new term – professionally oriented sectoral linguocultural studies. The theoretical and practical significance of our study lies in the introduction of a new special course "Sectoral Linguistics of Ukraine" into the educational space of higher education. The need for this course is especially felt in the teaching of professional terminology in the course "Ukrainian for Specific Purposes". Our proposals are based on examples of educational training of future healthcare professionals. The article highlights the techniques and methods of using professionally oriented linguistic and country studies in the educational process of higher education. We consider it expedient to offer such a course in higher education institutions of various fields of study, since professional "national" terms are available in many fields, broaden the worldview, develop students' linguistic and analytical skills.